Lean Transformation in Healthcare a Case Study at Skaraborgs Sjukhusgrupp - Ronge, Stefan (My University, 2015)
The quality of the Swedish healthcare has a prominent position internationally, but long queues for various treatments, are today often criticized and debated. However, patient queues and delays are often not the result of resource problems - they are the result of ow problems. The trend in recent years has been a knowledge transfer from the manufacturing industry to healthcare on how to create ow. Lean Manufacturing, which originates from the Toyota production system, has received a lot of attention. While Lean Manufacturing is a well described management framework, the proceeding to become \Lean", referred to as a \Lean Transformation" is considered more contextual. This study, conducted in 2010, investigates how to achieve sustainable Lean Transformations in the context of the Swedish healthcare system, with a focus on the patient ow through surgery departments. The methodology was designed as a qualitative case study, with a triangulation of data sources: a main case (KSS Sk ovde) and a reference case (SUS Lund), combined with the breadth of view from literature. In the main case, the author participated in a process improvement team as an action researcher. The reference case was investigated with interviews. The concrete measures identified on how to improve the patient ow, are very similar between the two cases, and are also well in line with basic Lean concepts. This suggests that other Swedish hospitals, who are in the beginning of a Lean transformation, have much to gain from studying the findings from others. The great challenge is however to create sustainability, which is basically a question of suitable leadership and cultural change. Even if these areas are less tangible, the issues and findings from the two cases have a lot in common, most of which references can be found in Lean literature. The report also discusses how Lean is not an option in the healthcare system - it is a necessity. Moreover, it is argued why the entrepreneurial drive is something that possibly needs attention in the healthcare Lean work, despite the Lean literature in general advocates the opposite.
Keywords: Övrig industriell teknik och ekonomi; Produktion; Transport; Other industrial engineering and economics; Production; Transport